2015
DOI: 10.3855/jidc.5976
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset prosthetic valve endocarditis caused by nontoxigenic Corynebacterium diphtheriae

Abstract: In developed countries, Corynebacterium diphtheriae infection is rare due to efficient immunization programs. However, cases of nontoxigenic strains of C. diphtheriae infections, including endocarditis, have been reported recently. Although the incidence remains low, these infections are associated with high morbidity and mortality. This report describes the first and atypical case of bacteremia and endocarditis caused by nontoxigenic C. diphtheriae var. gravis after introduction of immunization in the Kingdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…There are few cases of C. diphtheriae -infective endocarditis reported in the literature; a review by Muttaiyah et al 1 of the literature up to 2007 found 76 cases and our further literature search found an additional 6 reported cases 5–10. Interestingly, C. diphtheriae endocarditis cases predominantly occurred in persons <30 years of age 1.…”
Section: Discussionmentioning
confidence: 74%
“…There are few cases of C. diphtheriae -infective endocarditis reported in the literature; a review by Muttaiyah et al 1 of the literature up to 2007 found 76 cases and our further literature search found an additional 6 reported cases 5–10. Interestingly, C. diphtheriae endocarditis cases predominantly occurred in persons <30 years of age 1.…”
Section: Discussionmentioning
confidence: 74%
“…However, the vaccine does not prevent infections by non-toxigenic strains which can be highly aggressive. Due to its rarity, the medical literature presents non-toxigenic C. diphtheriae endocarditis mainly through case reports and reviews, with scarce descriptions of early embolic phenomena as acute ischemic strokes, vascular pseudoaneurysms and septic arthritis [3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…However, especially in developing countries, non-toxigenic C. diphtheriae strains are now emerging as cause of invasive disease like endocarditis, septic arthritis and osteomyelitis [1,2]. In fact, there is an increase in case reports of severe infection by nontoxigenic C. diphtheriae over the past few decades [3][4][5][6]. Non-toxigenic C. diphtheriae endocarditis has been related to the presence of valve prosthesis, use of injectable drugs and underlying cardiac disease.…”
Section: Introductionmentioning
confidence: 99%
“…Toksin üretimi olmadığında bile C.diphtheriae'nın bakteremi ve menenjit, endokardit, osteomiyelit, septik artrit, hepatit ve periferik embolik hastalık gibi ciddi komplikasyonlara yol açtığı bildirilmiştir 11,[15][16][17][18] . Toksijenik olmayan suşlarla invaziv enfeksiyonlar için immün yetmezlik, diyabet, kronik karaciğer hastalığı, konjenital ya da kalp kapak hastalıkları, intravenöz ilaç alışkanlığı, alkolizm gibi risk faktörleri söz konusudur.…”
Section: Discussionunclassified